HARNESSING ARTIFICIAL INTELLIGENCE FOR INNOVATIVE CUSTOMER RELATIONSHIP BUILDING: A MULTI-DIMENSIONAL ANALYSIS (CAHIERS MAGELLANES-NS, 2024)
Within the current business environment, the incorporation of Artificial Intelligence has surfaced as a paradigm-shifting phenomenon, offering prospects for novel strategies in cultivating consumer relationships. The purpose of this study is to perform a comprehensive examination that centres on the utilisation of artificial intelligence in the domain of customer relationship development. The purpose of the study is to determine the effect that A.I.-driven strategies have on the development of positive consumer relationships. Additionally, the research investigated whether the difficulties associated with A.I.-driven strategies had an impact on customers' perceptions of said strategies. The current investigation was carried out in the northern Kerala region, encompassing 362 retail firms of small and medium scale. Overall, the results indicated that A.I.-driven strategies assisted businesses in establishing positive customer relationships.